Cotton development and yield according to nitrogen application and cover crops - Ferrari, Samuel [UNESP]; Furlani Junior, Enes [UNESP]; Ferrari, Joao Vitor; Pereira, Gustavo Alves (Universidade Estadual de Londrina (UEL), 2011)
Nitrogen application on the cover and the maintenance of straw, conducted by direct seeding, should meet the needs of agriculture and promote soil conservation. This study evaluates the effect of pre-sowing nitrogen application in cotton crops and cover crops by direct seeding, on the development and yield of cotton. It was conducted in the municipality of Selviria-MS during the agricultural years 2005/06, 2006/07 and 2007/08. The experimental design used was a randomized block design consisting of three cover crops (forage turnip, black oat and white oat) and four nitrogen doses (0, 30, 60 and 90 kg of N ha(-1)) in pre-sowing of cotton. In April 2006, April 2007 and April 2008, the assessments of plant development and also harvesting of the experimental plots of cotton cultivars were conducted. The results showed that after planting the cover crops, the yield and development and the heights of cotton plants increased with the use of pre-sowing N of 90 kg ha(-1), also showing that the forage turnip is a coverage plant that provides increased cotton.
Keywords: Gossypium hirsutum; ammonium sulfate; cover crops and yield